The smear how shady political operatives and fake news control what you see, what you think, and how you vote - Attkisson, Sharyl 1961- (Harper, 2017)
The veteran journalist exposes the practices of opposition research to reveal how political leaders use their influence to shape public opinion, connecting popular misconceptions to strategic smear campaigns that have influenced voters